FUNCTIONAL-SEMANTIC ANALYSES OF PARTICIPLE I IN OLD ENGLISH TEXTS - Sokolova, A.Yu. (Russian Linguistic Bulletin, 2019)
The article presents the results of the functional-semantic analysis of participle I in the Old English texts. The study showed that all examples of the use of participle I in Old English texts can be divided into two groups. The first includes the use of participles with the noun. The second group includes examples of the functioning of the participle with verbs. The first group is traditionally referred to as attributive (or non-predicative) use of the participle. The second group includes cases of predicative use of the participle, that is, its functioning in the construction “S + V + PI”, where V is the finite form of a verb. In the construction “S + V + PI”, participle I can perform an attributive, substantive, adverbial, and predicative function, denoting a secondary action to the finite form of the verb.